Comparative performance of irrigated and rainfed agriculture in Ethiopia - Tilahun, H.; Erkossa, Teklu; Michael, M.; Hagos, Fitsum; Awulachew, Seleshi Bekele (2011)
With its an estimated human population of 85 million which increases annually at about 2.7 per cent, Ethiopia is the second most populous country in Sub-Saharan Africa (SSA) only after Nigeria. Agriculture contributes about 45% and 85% to the GDP and the export earnings, respectively. However, agriculture largely depends on the highly variable rainfall. Accentuated with the rampant land degradation, the seasonal and annual variation in rainfall severely impedes agricultural productivity. In the face of soaring global food prices, importing agricultural products is becoming more challenging. This entails a substantial increase in water and land productivity through investment in both rainfed and irrigated agriculture. Irrigation projects often require huge financial and capital investment. As a result, rain fed agriculture may continue to play a major role in the near future, especially in areas with sufficient rainfall. Therefore, prioritization and resources allocation to the rainfed and irrigated agriculture should ensure the efficient use of the limited resources. This study compared the efficiency of the small-scale irrigation (SSI) and the large-scale irrigated agricultural schemes in different river basins against the rain fed system. The study indicated that irrigated agriculture is more efficient both in terms of water use and economics regardless of the typology or the basins considered. The large-scale schemes are more efficient than the small-scale ones. This may be attributed to the use of other complementary crop management technologies such as fertilizers and the use of improved crop varieties. Although rainfed agriculture remains important for a long period to come, gradual transformation to irrigation particularly to largescale schemes may lead to efficient use of resources for economic development.